Individual Work of the Pupils - The Foundation of Development of Intellectual Skills - Bernotas, Vytautas (Acta Paedagogica Vilnensia, 1993)
The article primarily aims to look at the education of student’s autonomy, students’ individual work, in its historical aspect. It discusses ideas of J.A. Komensky, J.J. Rousseau, J. Dewey, who emphasized active teaching methods, building of research skills of students, self-sufficient problem-solving. Also, the article defines the basic characteristics of individual works, provides an example of a research work. Individual work can be classified by a number of features: a didactic aim, students’ cognitive activities, cognitive and mental operations. Forms of students’ independent work: experiments and tests, observations, work with a variety of knowledge sources – books, maps, documents, etc. It should be noted that students’ individual work should be diverse, systematically organized, taking into account students’ prior experience, skills of individual work. The teacher’s role becomes even more important in pupils’ in independent work – the teacher is confronted with new challenges. He becomes the organizer of the learning process rather than supplier knowledge.